2022
DOI: 10.21873/cgp.20313
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Differentiation of Embryoid Bodies and the Teratoma Subtype of Testicular Cancer

Abstract: Background: Testicular germ cell tumours (TGCTs) are the most frequent tumour type among young, adult men. TGCTs can be efficiently treated, but metastases of the teratoma subtype, for which there are no circulating biomarkers, represent a challenge. Materials and Methods: Global microRNA expression in teratoma tissue and embryoid bodies was assessed using next-generation sequencing. Levels of microRNAs identified as potential biomarkers were obtained from serum of patients with teratoma and matched healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…However, when compared to the control group, no significant differences in blood levels were discerned. On the other hand, miR-222-5p, miR-200a-5p, miR-196b-3p, and miR-454-5p were found to be ineffective in distinguishing teratoma from other conditions [39].…”
Section: Differentiating Teratomamentioning
confidence: 92%
“…However, when compared to the control group, no significant differences in blood levels were discerned. On the other hand, miR-222-5p, miR-200a-5p, miR-196b-3p, and miR-454-5p were found to be ineffective in distinguishing teratoma from other conditions [39].…”
Section: Differentiating Teratomamentioning
confidence: 92%
“…The authors did not find any other miR-NAs predictive of pure teratoma through small RNA sequencing. 101 One of the critical clinical needs in TGCTs remains the lack of a reliable circulating teratoma marker, 78,102 but this may not depend solely on miRNAs, but actually on the combination with additional epigenetic biomarkers. Recently, a method was reported that combined miR-371a-3p quantification by RT-qPCR and hypermethylated RASSF1A quantification by ddPCR in serum, which allowed detection of TGCT (including teratoma), with a combined sensitivity of 100%, in a cohort with 109 patient and 29 control samples.…”
Section: Tgcts: the Prototypical Example Of Mirnas Clinical Applicati...mentioning
confidence: 99%
“…In residual masses of metastatic non-seminomatous tumors, the new marker has been shown to identify those with residual vital cancer (25,26). However, the problem was that teratoma, which is present in about 30% of non-seminoma residual masses, does not express M371 (27)(28)(29). Thus, a negative M371 test in these cases will not obviate the need for postchemotherapy RPLND.…”
Section: Introductionmentioning
confidence: 99%